Quantitative Analysis of Borax in Cilok from Selected School-area Vendors in Seberang Ulu II, Palembang Using UV–Vis Spectrophotometry - Muhammad Fachri Falahi; Yanti Rosita; Putri Erlyn; Yuni Fitrianti (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Cilok is one of the most popular traditional street foods in Indonesia because of its chewy consistency, low price, and unique flavor. Despite its popularity, concerns regarding food safety remain, especially related to the misuse of hazardous additives such as borax. Based on the Regulation of the Indonesian Ministry of Health issued in 2012, the use of borax in food products is prohibited due to its harmful effects on human health. However, several studies have reported the continued presence of borax in traditional foods and snacks sold in the community. Therefore, this study was conducted to evaluate the physical characteristics of cilok suspected of containing borax and to measure borax concentrations quantitatively. Samples were obtained from selected vendors in the Seberang Ulu II district through purposive sampling with enrichment criteria. Borax analysis was performed using a curcumin-based UV–Vis spectrophotometric method. All collected samples showed diverse physical characteristics and were confirmed positive for borax contamination, with concentrations ranging from 2.84 to 56.28 mg/kg. These results demonstrate that borax is still being used in cilok sold by certain vendors in Seberang Ulu II, Palembang City. This condition suggests that food safety supervision by authorities, including the National Agency of Drug and Food Control and local Health Offices, has not yet achieved optimal effectiveness. Greater efforts are needed to strengthen policy implementation, improve routine monitoring, and increase educational campaigns for the public, particularly parents and school communities, in order to enhance the safety of street food products and safeguard public health.